Content teachers’ beliefs and attitudes toward working with multilingual learners through integrative approaches - Kim, Sujin; Park, Jung Yeon; Zhao, Manqian (Frontiers in Education, 2024)
The fast-growing population of multilingual learners (MLs) in U.S. schools calls for ML-focused instructional support from content classroom teachers to acquire content knowledge and language proficiency simultaneously. However, teachers in general lack competency in contentlanguage integrative pedagogy that builds on MLs' transliterate capabilities, placing MLs at a greater disadvantage in the content classroom. Given that teachers' classroom practices are shaped by their underlying language ideologies, it is important to examine what ideological beliefs and attitudes teachers are operating with for their day-to-day work with MLs. Framed by scholarship on content-language integrated instruction, language ideologies, and transliteracies approaches, this study examined content teachers' ideological beliefs and attitudes toward teaching MLs in the content classroom by accounting for the relations among the major constructs in the previously validated survey on content-language integrated education for MLs, the impact of several teacher-related variables on teachers' ideologies, and a group of selected teachers' perspectives toward the monolingual, separatist framework. This study employed a sequential mixed-methods design for a more comprehensive understanding of teachers' ideologies about working with MLs. Data analysis was based upon survey responses of inservice content teachers (N=100) and then focus group interviews (N=24). Results of a confirmatory factor analysis using a survey suggested that teachers who were more likely to endorse English-only monolingual pedagogy did not necessarily view themselves as having lesser sensitivity to MLs' backgrounds in their classroom. Results of regression analyses showed that teachers using pull-out or push-in instruction were more inclined to support language-integrated content teaching and considered themselves more sensitive to MLs' backgrounds than teachers who instruct specialized content. Interestingly, the specialized content teachers having a greater percentage of MLs in their classroom were more supportive of the language-integrated content teaching pedagogy than other teachers using the teaching role. Analysis of focus groups provided contextualized rationales for teachers' chosen stances toward the English-only monolingual, separatist pedagogy or the transliterate, integrative pedagogy for MLs. The findings demonstrated that teachers' ideologies were not merely individual beliefs but also intertwined with the hegemonic language ideologies of the larger education system. Implications for teacher development programs are discussed.